2020
DOI: 10.1371/journal.pone.0240172
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cytomegalovirus immune status and hearing loss outcomes in congenital cytomegalovirus-infected offspring

Abstract: The purpose of this study is to determine the relationship between maternal primary and recurrent CMV infection during pregnancy, symptoms at birth in the newborn, and long term hearing loss through18 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…In addition, the maternal history of CMV infection had no significant effect on the development of late‐onset SNHL in the current study. A previous study showed that SNHL commonly develops in patients with both symptomatic cCMV infection soon after birth and a history of maternal primary CMV infection 23 . We speculate that maternal CMV infection may produce early symptomatic cCMV infection rather than a late‐onset disorder.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, the maternal history of CMV infection had no significant effect on the development of late‐onset SNHL in the current study. A previous study showed that SNHL commonly develops in patients with both symptomatic cCMV infection soon after birth and a history of maternal primary CMV infection 23 . We speculate that maternal CMV infection may produce early symptomatic cCMV infection rather than a late‐onset disorder.…”
Section: Discussionmentioning
confidence: 69%
“…A previous study showed that SNHL commonly develops in patients with both symptomatic cCMV infection soon after birth and a history of maternal primary CMV infection. 23 We speculate that maternal CMV infection may produce early symptomatic cCMV infection rather than a late-onset disorder.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 87%
“…In a retrospective case study by Kim et al ( 16 ), 11 out of 58 children (19%) with cCMV had SNHL, but the majority of them were not identified as having hearing loss (HL) during the hospital hearing screening, suggesting SNHL can occur later in life for this population even after passing a newborn hearing screening. Demmler-Harrison et al ( 14 ) studied the long-term effects of cCMV-related HL, finding 20% of asymptomatic cCMV cases born with normal hearing to have late-onset SNHL. In a sample of 237 participants, 46% of children with primary cCMV were born with SNHL and 54% of children with primary cCMV had delayed onset SNHL, suggesting SNHL might not appear until up to 18 years of age for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, children identified as having hearing loss before 6 months of age are predicted to have increased speech and language performance compared to children identified after 6 months of age ( 3 ). Therefore, Demmler-Harrison et al ( 14 ) believe early identification of infants with symptomatic and asymptomatic cCMV is important for detecting SNHL and providing early monitoring and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, among the non-genetic causes of neurosensory deafness, congenital CMV infection ranks first, and is also the leading among the known viral causes of mental retardation. In about 10-15% of newborns, congenital CMV infection is accompanied by clinical symptoms, more often it is neurosensory deafness, increase in the size of internal organs, intracranial calcifications and chorioretinia [28,29].…”
Section: Review and Discussionmentioning
confidence: 99%